Invasive and Noninvasive Progression After Resection of Noninvasive Intraductal Papillary Mucinous Neoplasms. Issue 2 (17th August 2022) - Amini, Neda; Habib, Joseph R.; Blair, Alex; Rezaee, Neda; Kinny-Köster, Benedict; Cameron, John L.; Hruban, Ralph H.; Weiss, Matthew J.; Fishman, Elliot K.; Lafaro, Kelly J.; Zaheer, Atif; Manos, Lindsey; et al.
Abstract : Objective: To define frequencies, pattern of progression (invasive vs noninvasive), and risk factors of progression of resected noninvasive intraductal papillary mucinous neoplasms (IPMNs). Background: There is a risk of progression in the remnant pancreas after resection of IPMNs. Methods: Four hundred forty-nine consecutive patients with resected IPMNs from 1995 to 2018 were included to the study. Patients with invasive carcinoma or with follow-up <6 months were excluded. Noninvasive progression was defined as a new IPMN, increased main pancreatic duct size, and increased size of an existing lesion (5 mm compared with preoperative imaging). Invasive progression was defined as development of invasive cancer in the remnant pancreas or metastatic disease. Results: With a median follow-up of 48.9 months, progression was identified in 124 patients (27.6%); 108(24.1%) with noninvasive and 16(3.6%) with invasive progression. Median progression follow-up was longer for invasive progression (85.4 vs 55.9 months; P = 0.001). Five-and 10-year estimates for a cumulative incidence of invasive progression were 6.4% and 12.9% versus 26.9% and 41.5% for noninvasive progression. After risk adjustment, multifocality (HR 4.53, 95% CI 1.34–15.26; P = 0.02) and high-grade dysplasia (HGD) in the original resection (HR 3.60, 95% CI 1.13–11.48; P = 0.03) were associated with invasive progression. Conclusions: Progression to invasive carcinoma can occur years after the surgical resection of a noninvasive IPMN. HGD in the original resection is a risk factor for invasive progression but some cases of low-grade dysplasia also progressed to cancer. Patients with high-risk features such as HGD and multifocal cysts should be considered for more intensive surveillance and represent an important cohort for future trials such as anti-inflammatory or prophylactic immunotherapy.